2019
DOI: 10.1186/s12913-019-4164-4
|View full text |Cite
|
Sign up to set email alerts
|

The migration-related language barrier and professional interpreter use in primary health care in Switzerland

Abstract: Background With increased international migration, language barriers are likely becoming more relevant in primary care. The aim of this study was to investigate the language barrier in paediatric and adult primary care, present its consequences, reveal how it is overcome, as well as highlight the use of and potential unmet needs for professional interpreters, using Switzerland as a case study. Methods Primary healthcare providers were invited nation-wide to participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 32 publications
3
49
0
Order By: Relevance
“…Language discordance create what has been described as a "triple threat" to effective communication, as language differences not only hinder interaction but also act as a barrier due to their association with culture and often with low health literacy [3,4]. A growing body of research has documented a range of adverse effects of language discordance on quality of care, health outcomes, patient satisfaction, and costs [5][6][7][8][9]. Studies indicate that linguistic barriers result in inappropriate diagnoses, poorer adherence to treatment and follow-ups, more medication complications, more and often unnecessary diagnostic tests being ordered, and longer hospitalisations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Language discordance create what has been described as a "triple threat" to effective communication, as language differences not only hinder interaction but also act as a barrier due to their association with culture and often with low health literacy [3,4]. A growing body of research has documented a range of adverse effects of language discordance on quality of care, health outcomes, patient satisfaction, and costs [5][6][7][8][9]. Studies indicate that linguistic barriers result in inappropriate diagnoses, poorer adherence to treatment and follow-ups, more medication complications, more and often unnecessary diagnostic tests being ordered, and longer hospitalisations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, migrants with low Japanese language skills were less likely to undertake CISE. The language barrier is considered to be one of the main problems for migrants in acquiring information in a previous study also [34]. If an individual is unable to understand the language of the host country, he/she cannot collect information and utilize medical facilities despite having wishes to do so.…”
Section: Plos Onementioning
confidence: 99%
“…Using family members and friends as intermediaries is the most frequent way to overcome the language barrier -60.1%. Two thirds of doctors cannot use a professional interpreter when working with foreigners (Jaeger et al, 2019). At the same time, interviews with 21 first-generation migrant patients from Turkey in Holland showed that they trust informal interpreters more as the latter are perceived as defenders and lawyers because they communicate with patients as equals (Zendedel, Schouten, van Weert, & van den Putte, 2018).…”
Section: Specifics and Problems Of Medical Translationmentioning
confidence: 99%